Cutaneous Manifestations of Scleroderma: A Case Report - Tessa Thendria; Amira Suryani Rahmatika; Evy Ervianti; Dwi Murtiastutik; Trisiswati Indranarum; Hasnikmah Mappamasing; Septiana Widyantari (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Background: Scleroderma or systemic sclerosis is a rare multisystemic autoimmune disease characterized by vasculopathy, inflammation, and progressive fibrosis of the skin and multiple organs. Cutaneous manifestations and Raynaud’s phenomenon, usually becomes the initial presentation of scleroderma which noticed by the patient. Case: A 47-year-old-women presented with hardened and thickened skin on her arms and legs for 3 years which spreaded to her face and trunk. The lesions initially appeared as multiple red patches which progressed into white, thick and hard patches. The patient had history of recurrent Raynaud's phenomenon, dry cough, and shortness of breath. In the physical examination, the patient had skin hardening with salt and pepper appearance on her upper back and chest. The thoracic CT scan revealed interstitial lung disease. The patient diagnosed as definitive scleroderma based on The European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) criteria with score of 18. She has treated with methotrexate, methylprednisolone, topical corticosteroid and moisturizer. The skin lesion improved with the reduction of Rodnan skin score from 31 to 19 after 4 months of treatment. Conclusion: Cutaneous manifestation could be the early alarm and initial manifestation of scleroderma. As the pathology is deep beyond the skin, throughout examination should be performed to find any organ involvement. Dermatologist play a significant role in early identification of skin disorder and made multidiciplinary refferal. Early diagnosis and prompt treatment could reduce morbidity and mortality in scleroderma